Effect of the application of peanut shell, bamboo, and maize straw biochars on the bioavailability of Cd and growth of maize in Cd-contaminated soil - Zha, Yan; Zhao, Lin; Wei, Jiqian; Niu, Tianxin; Yue, Erkui; Wang, Xianbo; Chen, Yi; Shi, Jiang; Zhou, Tiefeng (Frontiers in Environmental Science, 2023)
Biochar is a versatile, carbon-rich, organic material that can effectively immobilize Cd in the soil. In this study, peanut shell biochar (SP), maize straw biochar (MS) and bamboo straw (BS) were applied in different proportions to evaluate its effects on the remediation of Cd-contaminated farmland soil and plant growth. The results revealed that both single and mixed applications of biochar substantially increased corn biomass and chlorophyll content compared to the unamended control treatment, while the malondialdehyde (MDA) and proline contents were largely unaffected. The bamboo straw block biochar with maize straw biochar at a mass ratio of 2:1 (DBM) has significantly increased the dry total biomass of maize (+107.24% compared to unamended soil). SP application has highly increased the SPAD value. PB with BS application at a mass ratio of 1:1 (MSB) has significantly decreased the soluble sugar content (+21.81% compared to unamended control soil).Soil pH was increased by the application of biochar alone and in combination with feedstocks. The soil content of Fe/Mn oxide-bound (OX) and exchangeable-bound Cd (EX) was decreased, whereas carbonate-bound Cd (CA), residue-bound Cd (RE), and organic-bound Cd (OM) contents increased.